Interface modification of sputtered NiOx as the hole-transporting layer for efficient inverted planar perovskite solar cells. Issue 6 (6th January 2020) - Zheng, Xiaolu; Song, Zhaoning; Chen, Zhiliang; Bista, Sandip Singh; Gui, Pengbin; Shrestha, Niraj; Chen, Cong; Li, Chongwen; Yin, Xinxing; Awni, Rasha A.; Lei, Hongwei; Tao, Chen; et al.
Abstract : An appropriately combined triple interface modification, i.e., post-annealing, O2 -plasma, and KCl treatments, is employed to ameliorate the optoelectronic properties of sputtered NiO x films and achieve better device performance. Abstract : Nickel oxide (NiO x ) as a hole-transporting layer (HTL) in perovskite solar cells (PSCs) has been studied extensively in recent years. However, unlike the solution-processed NiO x films, magnetron sputtered NiO x exhibits relatively low conductivity and imperfect band alignment with perovskites, severely limiting the device performance of PSCs. In this study, a synergistically combined strategy consisting of triple interface treatments – including post-annealing, O2 -plasma, and potassium chloride treatments – is employed to modulate the optoelectronic properties of the sputtered NiO x films. Through this approach, we successfully obtained NiO x films with increased carrier density and conductivity, better energy level alignment with the perovskite absorber layer, reduced interface trap density, and improved interfacial charge extraction. PSCs using this modified sputtered NiO x as the HTL deliver a highest stabilized efficiency of 18.7%. Our result offers an alternative method to manipulate sputtered NiO x thin film properties and thereby sheds light on a manufacturing pathway to perovskite solar cells featuring sputtered NiO x HTL.